2021
DOI: 10.1080/10495398.2021.1939042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein on growth performance, and serum biochemical index in late pregnant Hu ewes and their offspring

Abstract: The purpose of this study was to explore the effects of ewe growth performance, serum biochemical indicators and lamb growth and development at different protein levels in late pregnancy. A total of 15 pregnant ewes (46.4 ± 1.38kg initial BW) were assigned to 3 groups with 5 ewes in each group in a randomized block design. P1, P2 and P3 of three groups were fed diets with different levels of crude protein at 11.25%, 12.5% and 13.75% (low, medium and high) respectively, while the dietary energy levels remained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…In the current study, the concentration of GLU in the mixed group was significantly lower than in the PSR silage and corn silage treatments, while the higher ADG was observed in the mixed group. These results were inconsistent with previous studies, and this might be related to species and feed composition ( 11 15 ). The concentration of BUN is perceived as an effective indicator to measure the metabolism of protein and amino acid, low BUN level indicates high nitrogen metabolism capacity ( 21 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the current study, the concentration of GLU in the mixed group was significantly lower than in the PSR silage and corn silage treatments, while the higher ADG was observed in the mixed group. These results were inconsistent with previous studies, and this might be related to species and feed composition ( 11 15 ). The concentration of BUN is perceived as an effective indicator to measure the metabolism of protein and amino acid, low BUN level indicates high nitrogen metabolism capacity ( 21 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The PICRUSt prediction results showed that amino acid metabolism, carbohydrate metabolism, replication and repair, membrane transport, translation, and energy metabolism were the dominant gene families at KEGG level 2, all of which are essential for survival, growth, and reproduction of gastrointestinal microbes ( 44 ). These results were similar to our previous studies in sheep ( 11 15 ). Among these gene families, unexpectedly, the genes associated with metabolism of cofactors and vitamins, cellular processes and signaling, metabolism, biosynthesis of other secondary metabolites, infectious diseases, signaling molecules and interaction, nervous system, and digestive system were significantly higher in the PSR silage diet than in the mixed and corn silage diets, while lipid metabolism was dramatically lower in the PSR silage diet than in the corn silage diet.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The nutrient requirements, especially protein requirements for ewes increase dramatically during the last 2 months of pregnancy (the late gestation) because this stage achieves 80% of the fetal growth and the development of the mammary gland for colostrum production ( 1 ). Previous studies showed that the appropriate protein nutrition for ewes during pregnancy has a positive effect on ewes' postpartum weight, colostrum production ( 2 ), and lambs' birth weight ( 3 ), and thus contributes to neonatal growth and development ( 4 ). Therefore, it is important to study the effect of ewes' protein intake during late pregnancy on milk composition and offspring growth.…”
Section: Introductionmentioning
confidence: 99%